2015
DOI: 10.1634/theoncologist.2015-0097
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Molecular Tumor Board: The Impact on Treatment Decisions for 35 Patients Evaluated at Dartmouth-Hitchcock Medical Center

Abstract: Case evaluation by a multidisciplinary Molecular Tumor Board (MTB) is critical to benefit from individualized genetic data and maximize clinical impact. MTB recommendations shaped treatment options for the majority of cases evaluated. In the few patients treated with MTB-recommended therapy, disease outcomes were positive and support genetically informed treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 30 publications
3
75
1
1
Order By: Relevance
“…Among 50 patients, the MTB recommended therapy for 29 patients and only 9 received this therapy. In a similar report from the Dartmouth hospital in Lebanon, only 25% of patients received the treatment recommended by the MTB [29]. In the San Diego Moores Cancer Center, NGS analyses affected the cancer treatment in 35.3% of cases [30].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Among 50 patients, the MTB recommended therapy for 29 patients and only 9 received this therapy. In a similar report from the Dartmouth hospital in Lebanon, only 25% of patients received the treatment recommended by the MTB [29]. In the San Diego Moores Cancer Center, NGS analyses affected the cancer treatment in 35.3% of cases [30].…”
Section: Discussionmentioning
confidence: 95%
“…However, the integration of such technology in a practical, efficient, and value-added manner is not straightforward. Some reports are upcoming for American hospitals involving small and heterogenous population of patients with different cancer location [27][28][29][30][31]. While many clinical trials on this subject are in progress in European countries, no European hospital has reported their experience with such strategy in a daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Given the complex issues involved in interpreting these data sets, some institutions have adopted a ''molecular tumor board'' approach to facilitate multidisciplinary decision-making. [53][54][55] Although tumor profiling may reveal intriguing molecular targets for specific breast cancers and for breast cancer in general, current standards of care are not predicated on the results of NGS assays.…”
Section: Discussionmentioning
confidence: 99%
“…With this regard, as the clinical utility of comprehensive genomic profiling is just beginning to be evaluated, the number of publications reporting the clinical utility of comprehensive genomic profiling in cancer patients is still limited. Notwithstanding this, several previous studies have reported that comprehensive genomic profiling provided clinical benefit for patients with various advanced cancers (71)(72)(73)(74)(75). In a recent study by Tsimberidou et al (73), the overall survival of patients who received matched therapy was significantly longer than that of patients who did not received matched therapy (median, 11.4 vs. 8.6 months; P = 0.04).…”
Section: Clinical Utility Of Comprehensive Genomic Profilingmentioning
confidence: 99%